Migrants Living in the United Kingdom and Their Perceptions of Participation in Health Research: A Mixed‐Methods Study. - Gogoi, Mayuri; Baggaley, Rebecca F.; Silva, Luisa; Lal, Zainab; Reilly, Holly; Modhwadia, Vishant; Pan, Daniel; Bird, Paul; Nellums, Laura; Pareek, Manish (Health Expectations, 2025)
Background: Migrants' participation in health research is essential to give voice to their needs and inform evidence‐based practice. We conducted a mixed‐methods study with migrants living in Leicester, United Kingdom, to understand their perceptions of participation in health research and factors influencing participation. Methods: Our study included a questionnaire and focus groups with migrants. Interviews and focus groups were also conducted with key informants. The study was carried out at two sites in Leicester. Questionnaire data were analysed descriptively in R. The COM‐B framework was used to thematically analyse interview and focus group transcripts. Workshops with public members of migrant origin helped with data interpretation and analysis. Results: 119 questionnaires and 4 focus groups (n = 28) were completed with migrants. Seven interviews and one focus group (n = 7) were conducted with key informants. Questionnaire respondents originated from 34 different countries, with a significant proportion (25%) identifying themselves as asylum seekers/refugees. Migrants in the focus groups were from 16 different countries and were mainly asylum seekers/refugees (n = 18). The three components of the COM‐B model (Capability, Opportunity and Motivation) were identified as the main themes, and descriptive statistics from the questionnaire data have been used to supplement the 16 sub‐themes. Individual capabilities encompassing awareness and perception of research, language abilities and skills in the use of technology significantly influenced participation. Simultaneously, the presence or absence of opportunities such as costs, competing needs and priorities, healthcare access and experiences in the United Kingdom, language barriers, opportunities for learning and taking part, precarious living conditions and socio‐cultural norms and perceptions about health were found to be important for research participation. Motivations to take part in research included trust, context of the research, need‐based research, altruism, desire to be heard and receiving incentives. Conclusion: Our study contributes to the limited evidence base exploring migrants' participation in health research. Our findings, grounded in the COM‐B model, exhibit how migrants' motivations, influenced by a host of individual capabilities and environmental and social opportunities, can influence motivation and impact research participation behaviour. These findings may support the design of accessible, inclusive, equitable and impactful health research involving underserved groups. Patient or Public Contribution: Patient and Public Involvement and Engagement (PPIE) in the project was obtained through the EMBRACE (East Midlands Migrant Research Advisory Collaborative) group, which was created as a migrant specific advisory group in 2019. We recruited new migrant members into the group and involved them in the interpretation of the study results. We organised two workshops with the group, and in the first workshop, held in February 2024, nine members took part to review the preliminary results and offer insights in contextualising and interpreting the data. The research team took into consideration the feedback received at the workshop and integrated it into the analysis. The final analysis was presented to the group again in September 2024, and the discussions held at that workshop were instrumental in shaping this manuscript.